Design, Synthesis and Biological Evaluation of A Novel Class of Anticancer Agents: Anthracenylisoxazole Lexitropsin Conjugates - Han, Xiaochun (2008)
The synthesis and in vitro anti-tumor 60 cell lines screen of a novel series of anthracenyl isoxazole amides (AIMs) (22–33) is described. The molecules consist of an isoxazole that pre-organizes a planar aromatic moiety and a simple amide and/or lexitropsin-oligopeptide. The new conjugate molecules were prepared via doubly activated amidation modification of Weinreb’s amide formation technique, using SmCl(3) as an activating agent which produces improved yields for sterically hindered 3-aryl-4-isoxazolecarboxylic esters. The results of the National Cancer Institute’s (NCI) 60 cell line screening assay show a distinct structure activity relationship (SAR), wherein a trend of the highest activity for molecules with one N-methylpyrrole peptide. Evidence consistent with a mechanism of action via the interaction of these compounds with G-quadruplex (G4) DNA, and a structural based rational for the observed selectivity of the AIMs for G4 over B-DNA is presented.